Elimination of Medium/High Molecular Weight Solutes. Comparison of High Flow Hemodialysis with Extended Hemodialysis - Sánchez, Manuel Benítez; Barrero, Sergio; Silva, Maria R Da; Martinez, Carlos; Tirado, Guillermo Manuel; Cruz, Sonia (Journal of Clinical Nephrology, 2024)
Introduction: Post-dilution online hemodiafiltration is the most efficient extracorporeal depurative treatment of CKD. Recently a new type of membrane has been developed, with a higher cut-off point also called a medium cut-off point, which has the capacity to eliminate higher molecular weight molecules in hemodialysis. The hemodialysis performed with these membranes has been called “Expanded Hemodialysis”. Objective: Compare the purifying efficacy of medium and high molecular weight molecules in patients dialyzed with high-flux hemodialysis, VitaPES 210HF, and with patients treated with expanded hemodialysis with the medium cut-off dialyzer, Elisio-HX. We also assessed the effect that the increased removal of inflammatory mediators by MCO hemodialysis had on fecal Calprotectin levels. Patients and methods: This is a prospective observational cross-over study in which 8 prevalent hemodialysis patients were followed for two months. Blood levels of IL-6, C-reactive protein (CRP), β2-microglobulin, Kappa and Lambda immunoglobulin light chains, and serum albumin were determined before and after each hemodialysis session. Results: The percentage of reduction of medium and higher molecular weight molecules: β2microglobulin, IL-6, Kappa and Lambda chains and CRP were higher with the Elisio-21HX dialyzer compared to the VitaPES 210HF dialyzer. There was no difference in albumin clearance between the two dialyzers. Fecal calprotectin levels were lower in patients dialyzed with Elisio-21HX. Conclusion: The medium cutoff dialyzer, Elisio-HX, is more efficient in the elimination of medium/high molecular weight molecules than the VitaPES HF high-flux dialyzer, with the same albumin elimination. Improving inflammation at the local intestinal level with lower levels of fecal Calprotectin.